2021
DOI: 10.1080/23792949.2020.1851143
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban inequalities amplified by COVID-19: evidence from South Africa

Abstract: Like most governments around the world, the South African government adopted a uniform, place-blind response to the coronavirus pandemic, including a hard lockdown. New evidence from a large household survey reveals that the socioeconomic effects have widened pre-existing inequalities between cities and rural areas. More could be done to complement national relief programmes with targeted efforts to boost jobs and livelihoods in the most vulnerable areas. In addition, the premature withdrawal of relief measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 14 publications
3
35
0
2
Order By: Relevance
“…In three of our geographies, the economic shock was distributed similarly across the pre-pandemic wealth spectrum. This aligns with similar findings from national studies in Malawi, Nigeria, Ethiopia, Uganda and South Africa [ 24 , 27 , 29 , 31 ]. However, it diverges from findings in urban Ethiopia, [ 28 ] rural Uganda [ 30 ] and in Nigeria [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In three of our geographies, the economic shock was distributed similarly across the pre-pandemic wealth spectrum. This aligns with similar findings from national studies in Malawi, Nigeria, Ethiopia, Uganda and South Africa [ 24 , 27 , 29 , 31 ]. However, it diverges from findings in urban Ethiopia, [ 28 ] rural Uganda [ 30 ] and in Nigeria [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a study in rural communities in Uganda found that the negative economic effects were actually larger among households that were wealthier at baseline [ 30 ]. An analysis in South Africa found that the initial income effects were similar in urban and rural areas, but that urban areas experienced income and employment recovery at a higher rate, widening urban-rural inequality [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employment dropped sharply after lockdown was imposed, but by October 2020 the overall employment rate appeared to have recovered, although not for women or respondents with low levels of education. The provision of increased government support, including top-ups for existing unconditional grants (which ended after October) and the new, temporary Social Relief of Distress grant for working-aged adults with no other sources of support appeared to aid households, particularly those in rural areas [32]. However, the withdrawal of these grants has caused concern.…”
Section: Introductionmentioning
confidence: 99%
“…Other survey data suggested that as many as 3 million people who had been employed in February were unemployed (either temporarily or permanently) in June (Kean and Armstrong, 2020). The initial job losses affected urban and rural areas alike, although there was a modest recovery in urban areas in mid-year (Visagie and Turok, 2021).…”
Section: The South African Case: Large-scale But Temporary Provisionmentioning
confidence: 99%
“…The new emergency grant social grant also reached more rural than urban households -but the ratio was far smaller than for existing grants. In other words, the emergency grant was less strongly directed at the rural poor (Visagie and Turok, 2021). It is likely that the emergency unemployment insurance was heavily oriented to urban areas, given the structure of employment and unemployment.…”
Section: The South African Case: Large-scale But Temporary Provisionmentioning
confidence: 99%